Relief Stelae From Athens: The External Evidences Regarding Heracleia Pontica (The 5th to 4th Centuries B.C.) - Bora, Ali; Bora, Ali (Istanbul Univ, 2024)
Heracleia Pontica despite having such an important place in the ancient world, the settlement constitutes one of the areas in the southwestern Black Sea where the need for archaeological studies is felt intensely. Therefore the subject of the research constitutes the examination of our knowledge of the development of the Heracleia Pontica between the Archaic and Hellenistic periods (5th and 4th centuries BC). The evidences which are uncovered from an abroad polis is evaluated in the context of regional archaeology, and a group of finds consisting of funerary relief stelae and proxeny decrees revealed by Aegean archaeology- associated with Paphlagonian city- are discussed. These artifacts, dated between the 5th and 4th centuries BC were unearthed in Athens since the 19th century. The funerary relief stelae and proxeny decrees are unique in that they belong to the people from Heracleia as indicated in their inscriptions. Moreover, they form various arguments in examining the social turmoil, exiles, and commercial activities of the associated city or the relations between Athenai and Heracleia Pontica. The finds discussed in this study constituting four funerary relief stelae and two proxeny decrees are considered to be related to Heracleians based on the inscriptions. Although they belong to the Heracleians, the fact that they were unearthed in Athenai makes them particularly remarkable.
Relief Stelae From Athens: The External Evidences Regarding Heracleia Pontica (The 5th to 4th Centuries B.C.)
Keywords: Heracleia Pontica; Athens; Black Sea; Funerary Stelae; Archaeology